Casey A. Wood's Islamic Manuscripts in the McGill Libraries - Salamon, Anaïs (Papers of the Bibliographical Society of Canada / Cahiers de la Société bibliographique du Canada)

(untitled) (The Bibliographical Society of Canada/La Société bibliographique du Canada, 2022)
This paper aims to show how Casey Albert Wood’s passion for rare books and strong interest in the history of ophthalmology resulted in significant contributions to the development of the McGill Libraries’ collections. The first two parts will document the acquisition processes of the Ivanow and Meyerhof collections, highlight some of the codicological and paleographical characteristics of items in these collections, and explain how to navigate and access them today. The third part will focus on Wood’s Arabic-to-English translation of an eleventh-century eye treatise entitled Tadhkirat al-Kaḥḥālīn (“Memorandum Book of a Tenth-Century Oculist for the Use of Modern Ophtalmologist”)[1], often recognized as one of his greatest contributions to the field of the history of ophthalmology. The fourth and concluding part will describe the unique and remarkable collection of original manuscripts of the Tadhkirat al-Kaḥḥālīn collected and presented to the McGill Library by Casey A. Wood.[1]  Casey Wood’s translation.